2020
DOI: 10.3928/1081597x-20200226-03
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Keratoconus and Thyroid Gland Dysfunction: A Cross-Sectional Case–Control Study

Abstract: K eratoconus is a corneal ectatic disorder that starts at puberty and decreases the radius of curvature of the central cornea. 1 Kennedy et al. 2 reported that the incidence rate is 1 per 50,000 among the population. Moreover, the pathophysiological processes underlying keratoconus have not been fully explained and proposed mechanisms including oxidative dam-age, proteolytic degradation in the corneal stroma, epithelial mechanical injury, immunological factors, and genetic factors have been suggested. [1][2][3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 25 publications
0
16
1
Order By: Relevance
“…Some authors reported that hypothyroidism might be associated with corneal ectasia and could be one of the casual factors, but the recent studies on the association between thyroid gland dysfunction and KC reported conflicting results. 1520,26,27…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some authors reported that hypothyroidism might be associated with corneal ectasia and could be one of the casual factors, but the recent studies on the association between thyroid gland dysfunction and KC reported conflicting results. 1520,26,27…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Alhawari et al 19 did not find statistically significant association between autoimmune thyroiditis and keratoconus. Recently El-Massry et al 20 conducted a cross-sectional case-control study including 187 patients with keratoconus without previously diagnosed thyroid gland dysfunction and 187 healthy controls. The authors showed significant difference between prevalence of thyroid gland dysfunction in the KC group (5.35%) as compared to the control (1.1%) and hypothized a possible association between KC and thyroid disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The contribution of thyroid hormones is still under scrutiny. Some studies have reported a higher thyroid gland dysfunction prevalence among KC patients [72,73], but others failed to prove an association between them [74][75][76]. Nevertheless, increased levels of thyroxine hormone (T4) were found in tears [72,77] and aqueous humor [78].…”
Section: Thyroid Hormonesmentioning
confidence: 99%
“…Hormonal changes in the body are known to influence KC pathogenesis and progression. Thyroid related disease and other hormonal disorders can be associated with KC [47]. Hormonal changes during pregnancy can lead to biomechanical changes in the cornea and progression of keratoconus [48].…”
Section: Hormonesmentioning
confidence: 99%